2015
DOI: 10.1111/cbdd.12488
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nucleoside Analogs as Inducers of Neuronal Differentiation in a Human Reporter Cell Line and Adult Stem Cells

Abstract: Nucleoside analogs (NSAs) were among the first chemotherapeutic agents and could also be useful for the manipulation of cell fate. To investigate the potential of NSAs for the induction of neuronal differentiation, we developed a novel phenotypic assay based on a human neuron-committed teratocarcinoma cell line (NT2) as a model for neuronal progenitors and constructed a NT2-based reporter cell line that expressed eGFP under the control of a neuron-specific promoter. We tested 38 structurally related NSAs and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Stem cells play a pivotal role in the human body for tissue regeneration and they are now used as an integral part of modern clinical treatment . Over the past decades, numerous attempts are devoted toward neural differentiation of stem cells . Various sources of stem cells such as neural stem cells (NSCs) or neural progenitor cells (NPCs) have been studied for treatment of SCI and varying levels of improvement in animal models have been demonstrated .…”
Section: Introductionmentioning
confidence: 99%
“…Stem cells play a pivotal role in the human body for tissue regeneration and they are now used as an integral part of modern clinical treatment . Over the past decades, numerous attempts are devoted toward neural differentiation of stem cells . Various sources of stem cells such as neural stem cells (NSCs) or neural progenitor cells (NPCs) have been studied for treatment of SCI and varying levels of improvement in animal models have been demonstrated .…”
Section: Introductionmentioning
confidence: 99%
“…In a series of precedent publications we and others have demonstrated that the cancerostatic/cancerotoxic activity of pyrimidine ß‐ d ‐ribonucleoside antimetabolites such as 5‐fluorouridine and 6‐azauridine towards different human tumor cell lines as well as neurobiological and antiviral activities can be significantly improved by lipophilization. Also, regular, canonical pyrimidine ß ‐ d ‐ribonucleosides such as uridine and 5‐methyluridine acquire a surprisingly high antitumor in vitro activity upon covalent hydrophobization .…”
Section: Introductionmentioning
confidence: 99%